Indicators used in the dominace of adolescent masculinity in secondary educations: The importance of «should be» a man - Ceballos Fernández, Marta (Última Década, 2020)
The article examines the construction of «masculinity» according to the interpretation that male students-fourth grade of Secondary Education (ESO) which they offer around the male gender identity. The study involved three schools of the Principality of Asturias (Spain). Effective use of a qualitative methodology, based on focus groups and individual interviews, conducted by the relevant discourse analysis. The results indicate that men respect the requirements to develop a normative male-hegemonic view on masculinity, and displayed in the following indicators: heterosexuality, exaltation of the body as an active agent and, finally, emotional silence. This data shows the prevalence of gender stereotyping in young men, justifying the importance to pedagogically intervene in this area.